ICT teacher professional development in intercultural contexts. The experience of the Baccalaureate in Education Sciences, I and II cycles, with an emphasis on language and Cabecar culture (Innovaciones Educativas, 2021)
The experience of the educational process in the use of information and communication technologies (ICT), implemented in the project that imparts the interuniversity career of baccalaureate in Education Sciences I and II Cycles, with an emphasis on Language and Culture Cabécar, is taken as an object of study to identify findings that contribute to the construction of an improved and updated proposal for the offer of the third cohort. It specifically addresses professional development for the acquisition of teaching skills in the use of ICT, which has been revealed, in the Eighth State of Education report (2021), as one of the deficit areas in teaching staff. The choice of this area lies in the importance that teachers achieve an adequate use of ICT for the development of educational processes and the achievement of their educational goals, with ethical use, which transcends in student training. This analysis is complemented by the study of theoretical and practical proposals around teacher professional development, without neglecting the intercultural context of the project. The experience of the educational process in the use of information and communication technologies (ICT), implemented in the project that imparts the interuniversity career of baccalaureate in Education Sciences I and II Cycles, with an emphasis on Language and Culture Cabécar, is taken as an object of study to identify findings that contribute to the construction of an improved and updated proposal for the offer of the third cohort. It specifically addresses professional development for the acquisition of teaching skills in the use of ICT, which has been revealed, in the Eighth State of Education report (2021), as one of the deficit areas in teaching staff. The choice of this area lies in the importance that teachers achieve an adequate use of ICT for the development of educational processes and the achievement of their educational goals, with ethical use, which transcends in student training. This analysis is complemented by the study of theoretical and practical proposals around teacher professional development, without neglecting the intercultural context of the project.
Keywords: Teacher training; teacher skills; educational technology; intercultural education; cabecar; professional development